Rehabilitasi Napi Teroris Melalui Program Deradikalisasi - Kurniawan, Andi; Darwis, Abdul Malik Fajar (Fakultas Syariah INSURI Ponorogo, 2023)
Deradicalization is ah program given toinmate kasus of terrorism within the Institutioncorrectional (LAPAS) with prevention efforts andneutralize notionsradicals that are considered dangerousand can causesecurity threat in ancountry. Deradi approachcalization can be with psychology,religion, law, educationin national humanity andstate as well as social and cultural. deradicalization program aims to drivereturn of the terrorist convictsthose affected by radical understanding to return to the path thatGoodand right. Builder programn deradicalization is veryit's important to apply, becausena see lately caseTerrorists have become material international discussionbecause it is a crimewhich can be threateningnational security for loyalp countries around the world, thenfrom that the deradicalization programthis is one wayto prevent it from happeningterror cases and can suppressand neutralize yousus terrorism and radicalism(radicalism). The results of this study describe[i-[2] handling of groups that have radical understanding or in this case are terrorists, through a deradicalization program requires clear regulations or arrangements accompanied by the involvement of relevant agencies based on a legal basis or foundation, because deradicalization that runs well and is integrated is needed in carrying out prevention to continue the growth of theoretical movements and radical understanding in Indonesia.